1998
DOI: 10.1038/3855
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin A1 is required for meiosis in the male mouse

Abstract: The mammalian A-type cyclin family consists of two members, cyclin A1 (encoded by Ccna1) and cyclin A2 (encoded by Ccna2). Cyclin A2 promotes both G1/S and G2/M transitions, and targeted deletion of Ccna2 in mouse is embryonic lethal3. Cyclin A1 is expressed in mice exclusively in the germ cell lineage and is expressed in humans at highest levels in the testis and certain myeloid leukaemia cells. To investigate the role of cyclin A1 and possible redundancy among the cyclins in vivo, we generated mice bearing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
295
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(307 citation statements)
references
References 23 publications
10
295
0
2
Order By: Relevance
“…Many of these genes encode proteins specifically involved in the control of the meiotic cell cycle, such as cyclin A1 (Table 2) (Liu et al, 1998), cdk4-inhibitors p18 and p19 (Table 2) (Zindy et al, 2001), A-myb (Table 2) (Toscani et al, 1997), Nek2 (Table 9) (Di Agostino et al, 2002), but in many cases their expression reflects meiotic accumulation of transcripts destined to be translated later during spermiogenesis, such as testis-specific lactate dehydrogenase (Table 7) (Li et al, 1998), testis-specific poly(A) polymerase b (Table 8) Kashiwabara et al, 2002), calmegin (Table 9) (Ikawa et al, 1997), preproacrosin (Table 5) (Kremling et al, 1991), fertilin b (Table 5) (Cho et al, 1998), Trf2 (Table 3) (Martianov et al, 2001), MSJ-1 (Table 5) (Berruti and Martegani, 2001), Tpx1 (Table 5) (Kasahara et al, 1989), Tekt1 (Table 5) (Larsson et al, 2000), Tesp1 (Table 5) (Kohno et al, 1998) and so on. It is noteworthy that the spermatocyte-specific expression of a large number of genes encoding enzymes is involved in glycolysis and gluconeogenesis, beside that of Pgk2, encoding a well known meiotic isoform of phosphoglycerate kinase (Boer et al, 1987) (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these genes encode proteins specifically involved in the control of the meiotic cell cycle, such as cyclin A1 (Table 2) (Liu et al, 1998), cdk4-inhibitors p18 and p19 (Table 2) (Zindy et al, 2001), A-myb (Table 2) (Toscani et al, 1997), Nek2 (Table 9) (Di Agostino et al, 2002), but in many cases their expression reflects meiotic accumulation of transcripts destined to be translated later during spermiogenesis, such as testis-specific lactate dehydrogenase (Table 7) (Li et al, 1998), testis-specific poly(A) polymerase b (Table 8) Kashiwabara et al, 2002), calmegin (Table 9) (Ikawa et al, 1997), preproacrosin (Table 5) (Kremling et al, 1991), fertilin b (Table 5) (Cho et al, 1998), Trf2 (Table 3) (Martianov et al, 2001), MSJ-1 (Table 5) (Berruti and Martegani, 2001), Tpx1 (Table 5) (Kasahara et al, 1989), Tekt1 (Table 5) (Larsson et al, 2000), Tesp1 (Table 5) (Kohno et al, 1998) and so on. It is noteworthy that the spermatocyte-specific expression of a large number of genes encoding enzymes is involved in glycolysis and gluconeogenesis, beside that of Pgk2, encoding a well known meiotic isoform of phosphoglycerate kinase (Boer et al, 1987) (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Gene disruption revealed that cyclin A1 is required for the meiotic progression of male germ cells in mice (Liu et al, 1998). Recent findings also suggest that, in normal meiotic male germ cells in mice, cyclin A1 participates in the regulation of protein kinases such as cdc25s or phosphatases, critical to the G2-M transition, probably through involvement in the initial amplification of MPF by means of the activation of cdc25-phosphatase phosphorylation (Liu et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Studies of A-type cyclins in mammalian gametogenesis indicate that cyclin A2 is expressed from the spermatogonium stage to the preleptotene spermatocyte stage and that cyclin A1 is expressed only from the pachytene spermatocyte stage to the end of meiotic division (Sweeney et al, 1996). Furthermore, cyclin A1 is required for the entry of spermatocytes into the first meiotic division in male mice (Liu et al, 1998). Although it is known that two distinct A-type cyclins (A1 and A2) are present, information on the activities of these two cyclins during gametogenesis is scarce, and, with respect to spermatogenesis, it is generally limited to mice.…”
Section: Introductionmentioning
confidence: 99%
“…21 We detected meiotic induction of cyclin A1 and CDK2, which are essential for spermatogenesis but not for mitosis. [9][10][11][12] CDKN2c (p18 INK4c ) and CDKN2d (p19 INK4d ), whose expression also markedly increased, conferred infertility to double-knockout mice. 19 In contrast, CDKN1b (p27 KIP1 ) expression was almost absent in our analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We created transgenic mice that expressed both b-galactosidase and EGFP under the control of the murine and the human cyclin A1 promoter, respectively. 12,14,26 Expression of the reporter genes was then analyzed in adjacent testis sections prepared from mice at postnatal days 1,4,8,11,14,18,21,26 and 34 by X-gal staining (b-galactosidase) and fluorescence microscopy (EGFP; Fig. 6a).…”
Section: Human and Murine Cyclin A1 Promoter Activity In Testis Develmentioning
confidence: 99%